PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. ANUGERAH NIAGA SAWINDO SEI JERNIH KABUPATEN ROKAN HULU - -, Ideranesti (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
Abstract This study aims to determine the effect of supervision of the work productivity of employees at PT. Anugerah Niga Sawindo Sei Jernih Kabupaten Rokan Hulu. This research uses a method of sampling saturated or census with a population of 55 people. Source of data used are primary data and secondary data analysis technique used is a simple linear regression and ujihipotesis using test T-test and test correlation coefficient and coefficient of determination. The data were processed using SPSS windows version 18, produces the following regression equation: Y = 20.174 + 0,388X of this research can be concluded that based on the statistical result that the control variable effect on productivity. From this research obtained value adjusted R2 of 0.465, it means that 46.5% control effect on employee productivity. Sememtara the rest is contributed by other factors. Management should pay more attention perusahaa greater scrutiny of every activity of the company and do not forget to give motivation so easy to achieve employee productivity maxsimal in accordance with a plan agreed upon by all agencies of the company.Â